Interactions between Grape Maturity Indices and Quality for Pinotage and Cabernet Sauvignon Wines from Four Localities - Van Rooyen, P.C.; Ellis, L.P.; Du Plessis, C.S. (South African Journal of Enology and Viticulture, 2017)
Three grape maturity indices viz. degrees Balling (OB), OB total titratable acid (TT A) ratio and the OB.pH product of musts were compared regarding their ability to predict optimum quality for Cabernet Sauvignon and Pinotage wines. Comprehensive analytical data from 128 musts and corresponding wines for the 1979 and 1980 vintages from the Stellenbosch, Durbanville, Lutzville and Robertson areas were subjected to principal component analysis using variables and variable ratios selected by correlation to quality weighting. The results indicated that 0B alone could not perform the function of a grape maturity index for predicting optimum quality. In the case of the OB/TT A index, the range wherein maximum wine quality occurred was too wide to be of practical value in this instance. The 0B.pH index gave a narrower optimum range, and in contrast to the two other indices gave similar results for both cultivars.